2019
DOI: 10.1002/ecs2.2536
|View full text |Cite
|
Sign up to set email alerts
|

On the geography of activity: productivity but not temperature constrains discovery rates by ectotherm consumers

Abstract: Consumer activity—the rate that individuals move through and discover items in their environment—can constrain population interactions and ecosystem services. We introduce a model that assumes consumer activity is co‐limited by the abundance and velocity of consumers, which in turn are constrained by two global drivers: net primary productivity (NPP) and environmental temperature, respectively. We test it with data from a recent study showing how arthropod activity decreases with latitude and elevation. The ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 28 publications
(55 reference statements)
1
22
0
Order By: Relevance
“…Previous studies have shown that ant abundance is higher in less seasonal and more productive environments (e.g. Kaspari et al, 2000; Kaspari & de Beurs, 2019). This may be because ants are able to harvest more energy due to their foraging for longer periods throughout the year in more climatically stable environments (Kaspari et al, 2000).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Previous studies have shown that ant abundance is higher in less seasonal and more productive environments (e.g. Kaspari et al, 2000; Kaspari & de Beurs, 2019). This may be because ants are able to harvest more energy due to their foraging for longer periods throughout the year in more climatically stable environments (Kaspari et al, 2000).…”
Section: Discussionmentioning
confidence: 92%
“…This may be because ants are able to harvest more energy due to their foraging for longer periods throughout the year in more climatically stable environments (Kaspari et al, 2000). In addition, there is greater energy and carbon availability for individuals in more productive environments, which also increases abundance (Kaspari & de Beurs, 2019). Thus, higher ant abundances may also be correlated with greater foraging activity in productive environments with low‐temperature seasonality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found a weak trend ( r 2 = .04) in the opposite direction. It is possible that, for a given amount of plant Na in a grassland ecosystem, further increasing animal biomass provides other nutrients such as protein, fat, lipids and minerals that may be co‐limiting (Kaspari & de Beurs, ). If true, it would suggest that experimentally adding necromass (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Ants were the main arthropod predator in our boreal site; several nests of Formica aquilonia were located within the study area, and some of them were as close as two meters from the experimental plants. In the tropics, arthropod predation in tree crowns is also dominated by ants, but their abundance, diversity and activity are considerably higher there than in other environments (Jeanne 1979;Floren et al 2014;Kaspari and de Beurs 2019). Some researchers raise concerns about whether arthropod predators perceive modelling clay caterpillars as real prey because the models do not possess the chemical cues important for prey recognition by many invertebrate predators (Vet and Dicke 1992).…”
Section: Between-site Differences In Predation Ratesmentioning
confidence: 99%